S3 guideline for actinic keratosis and cutaneous squamous cell carcinoma (cSCC) – short version, part 2: epidemiology, surgical and systemic treatment of cSCC, follow‐up, prevention and occupational disease. (4th April 2020) - Leiter, Ulrike; Heppt, Markus V.; Steeb, Theresa; Amaral, Teresa; Bauer, Andrea; Becker, Jürgen C.; Breitbart, Eckhardt; Breuninger, Helmut; Diepgen, Thomas; Dirschka, Thomas; Eigentler, Thomas; Flaig, Michael; et al.
Summary: Actinic keratoses (AKs) are common lesions in light‐skinned individuals that can potentially progress to cutaneous squamous cell carcinoma (cSCC). Both conditions may be associated with significant morbidity and constitute a major disease burden, especially among the elderly. To establish an evidence‐based framework for clinical decision making, the guidelines for actinic keratosis and cutaneous squamous cell carcinoma were developed using the highest level of methodology (S3) according to regulations issued by the Association of Scientific Medical Societies in Germany (AWMF). The guidelines are aimed at dermatologists, general practitioners, ENT specialists, surgeons, oncologists, radiologists and radiation oncologists in hospitals and office‐based settings as well as other medical specialties involved in the diagnosis and treatment of patients with AKs and cSCC. The guidelines are also aimed at affected patients, their relatives, policy makers and insurance funds. In the second part, we will address aspects relating to epidemiology, etiology, surgical and systemic treatment of cSCC, follow‐up and disease prevention, and discuss AKs and cSCC in the context of occupational disease regulations.